### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

dbl(0) → 0
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0, cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(2n):
The rewrite sequence
from(n__from(X13499_3)) →+ cons(from(X13499_3), n__from(n__s(from(X13499_3))))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [X13499_3 / n__from(X13499_3)].
The result substitution is [ ].

The rewrite sequence
from(n__from(X13499_3)) →+ cons(from(X13499_3), n__from(n__s(from(X13499_3))))
gives rise to a decreasing loop by considering the right hand sides subterm at position [1,0,0].
The pumping substitution is [X13499_3 / n__from(X13499_3)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
dbl, activate, dbls, sel, from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (8) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

The following defined symbols remain to be analysed:
activate, dbl, dbls, sel, from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Induction Base:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, 0)))

Induction Step:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, +(n4_0, 1)))) →RΩ(1)
dbl(activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0)))) →IH
dbl(*3_0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

The following defined symbols remain to be analysed:
dbl, dbls, sel, from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (12) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol dbl.

### (13) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

The following defined symbols remain to be analysed:
dbls, sel, from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (14) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol dbls.

### (15) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

The following defined symbols remain to be analysed:
sel, from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (16) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol sel.

### (17) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

The following defined symbols remain to be analysed:
from

They will be analysed ascendingly in the following order:
dbl = activate
dbl = dbls
dbl = sel
dbl = from
activate = dbls
activate = sel
activate = from
dbls = sel
dbls = from
sel = from

### (18) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol from.

### (19) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

No more defined symbols left to analyse.

### (20) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

### (22) Obligation:

TRS:
Rules:
dbl(0') → 0'
dbl(s(X)) → s(n__s(n__dbl(activate(X))))
dbls(nil) → nil
dbls(cons(X, Y)) → cons(n__dbl(activate(X)), n__dbls(activate(Y)))
sel(0', cons(X, Y)) → activate(X)
sel(s(X), cons(Y, Z)) → sel(activate(X), activate(Z))
indx(nil, X) → nil
indx(cons(X, Y), Z) → cons(n__sel(activate(X), activate(Z)), n__indx(activate(Y), activate(Z)))
from(X) → cons(activate(X), n__from(n__s(activate(X))))
s(X) → n__s(X)
dbl(X) → n__dbl(X)
dbls(X) → n__dbls(X)
sel(X1, X2) → n__sel(X1, X2)
indx(X1, X2) → n__indx(X1, X2)
from(X) → n__from(X)
activate(n__s(X)) → s(X)
activate(n__dbl(X)) → dbl(activate(X))
activate(n__dbls(X)) → dbls(activate(X))
activate(n__sel(X1, X2)) → sel(activate(X1), activate(X2))
activate(n__indx(X1, X2)) → indx(activate(X1), X2)
activate(n__from(X)) → from(X)
activate(X) → X

Types:
dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
0' :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__s :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbl :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
activate :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
nil :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
cons :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__dbls :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__sel :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__indx :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
n__from :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
hole_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from1_0 :: 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0 :: Nat → 0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from

Lemmas:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)

Generator Equations:
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(0) ⇔ 0'
gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(x, 1)) ⇔ n__dbl(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(x))

No more defined symbols left to analyse.

### (23) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
activate(gen_0':n__dbl:n__s:nil:cons:n__dbls:n__sel:n__indx:n__from2_0(+(1, n4_0))) → *3_0, rt ∈ Ω(n40)